Producing ownership through play: everyday public space practices in the Frankenberger neighbourhood - Işık, Pelin; Reicher, Christa (Journal of Architecture and Urbanism, 2026)
Play is commonly associated with childhood as a creative and productive activity that supports learning and innovation. However, its relevance extends beyond childhood and offers a critical lens for examining the consumption-oriented and rationalised patterns of contemporary urban life. In public space, playful activities often emerge as spontaneous and voluntary practices through which individuals engage with their surroundings, develop a sense of belonging, participate in shaping everyday spatial use, and move beyond purely functional or passive interpretations of space. In this article, owning space is understood not as a legal or formal condition, but as a situational and experiential process enacted through everyday use, interaction, and spatial adaptation by city residents. Such practices demonstrate how public space can be actively produced through use rather than passively consumed, and how everyday activities may resist tendencies toward standardisation and privatisation. This study investigates the relationship between play theory and urban public space through a case study of the Frankenberger Neighbourhood in Aachen. Moving beyond playground-based and child-centred interpretations of play, the research focuses on playful and social practices embedded in everyday public space use, while critically engaging with processes of privatisation and control. The study draws on systematic observations, behavioural mapping, visual documentation, and questionnaires designed to explore users’ preferences, choices, and expectations regarding public space. Together, these methods illustrate how residents participate in and activate public space through playful practices, how owning space is produced through everyday use, and how such insights can inform public space design. The article argues that urban designers and planners can support more inclusive and playful public spaces not by prescribing specific functions, but by enabling spatial conditions that allow users to shape, reinterpret, and co-produce space through their everyday practices.